Pendampingan Sistem Penggajian Pegawai Negeri Sipil Pada Kantor Kecamatan Bogor Barat Kota Bogor - Septian Cahyadi; Toni Andrianto; Ayu Nanda Apriyanti (Jurnal Abdimas Dedikasi Kesatuan, 2020)
Salary Is a payment for the delivery of services performed by employees who work for one month. Payroll has a very important role. This is because the payroll portion concerns the survival of the company. To overcome the misappropriation of payroll and so that the payroll process runs well, a reliable and accurate payroll system and procedure is needed to determine the steps that must be taken during the payroll process and also to provide documents used in employee payroll. The purpose of this discussion is to find out how the payroll system and the civil servant payroll procedure at Kecamatan West Bogor of Bogor City as well as the documents used in the payroll The results of the discussion showed that Kecamatan west Bogor had carried out payroll systems and procedures well in accordance with the stages and applicable government regulations. Documents used in the remuneration have been done well, such as supporting documents on salary changes, hourly attendance cards, payroll, recapitulation of payroll, salary statements, and proof of cash out. The stipulations in the composition of salary payments can be justified to be used as a basis for the determination of the payroll system and procedures for providing employee salaries every month. Keywords: Payroll System and Procedure, Kecamatan West Bogor